Modelling consumers' payment behaviour towards contactless cards. (26th November 2021) - Saprikis, Vaggelis; Vlachopoulou, Maro; Markos, Angelos
Mobile payment technologies have led the development of an open and collaborative payment ecosystem, where financial institutions and merchants have provided innovative solutions to conduct business with consumers. One of these new evolving payment alternatives is contactless card that incorporates near field communication technology, enabling consumers to make everyday purchases quickly and safely especially for low-value transactions. Based on the technology acceptance model, innovation diffusion theory, and the relevant literature, nine variables - perceived usefulness, perceived ease of use, trust, convenience, social influence, compatibility, anxiety, security and innovativeness - are proposed to help predict consumers' behavioural intention to pay by a contactless card. The results and implications of our study contribute to an expanded understanding of the factors that influence consumers' behaviour towards their use and provide valuable information to all involved parties - individuals, merchants and financial institutions - about how consumers perceive this technology.